2012
DOI: 10.1111/j.1365-2966.2012.21726.x
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic study of planetary nebulae in the dwarf irregular galaxy IC10

Abstract: We present positions, kinematics and the planetary nebula luminosity function (PNLF) for 35 planetary nebulae (PNe) in the nearest starburst galaxy IC10 extending out to 3 kpc from the galaxy's centre. We take advantage of the deep imaging and spectroscopic capabilities provided by the Faint Object Camera and Spectrograph on the 8.2 m Subaru Telescope. The PN velocities were measured through the slitless‐spectroscopy technique, which allows us to explore the kinematics of IC10 with high precision. Using these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…7) consist exclusively of FSR 486 stars. The derived distance modulus to IC 10 in previous works is larger than 24 mag (Borissova et al 2000;Hunter 2001;Sanna et al 2008;Gonçalves et al 2012). However, we derive a distance modulus of ≈ 14 mag for FSR 486.…”
Section: Fsr 486 and The Dwarf Galaxy Ic 10mentioning
confidence: 62%
“…7) consist exclusively of FSR 486 stars. The derived distance modulus to IC 10 in previous works is larger than 24 mag (Borissova et al 2000;Hunter 2001;Sanna et al 2008;Gonçalves et al 2012). However, we derive a distance modulus of ≈ 14 mag for FSR 486.…”
Section: Fsr 486 and The Dwarf Galaxy Ic 10mentioning
confidence: 62%
“…carried out by Gonçalves et al (2012), who reported that there is a kinematical connection between both populations in IC 10. Several authors have also used the PN population to analyze the kinematics of elliptical galaxies, for example, Mc Neil-Moylan et al (2012), Teodorescu et al (2011), and Coccato et al (2009) have analyzed PNe kinematics in ellipticals at about 20 Mpc, and Ventimiglia et al (2011) and Gerhard et al (2007) have studied ellipticals at 50-100 Mpc.…”
Section: Introductionmentioning
confidence: 98%
“…This indicates that IC 10 is forming massive stars at the same rate as a star-forming region in a spiral galaxy, such as M33, throughout its disk. Gonçlaves et al (2012) used the Subaru telescope to study the kinematics of 35 planetary nebulae in IC 10 that traced the stellar motions. They concluded that the planetary nebulae generally follow the same kinematic trends as the gas, as measured by Very Large Array 2 (VLA), including the kinematics of some of the outer, counterrotating gas.…”
Section: Introductionmentioning
confidence: 99%